Suporte social e adesão ao tratamento antirretroviral de adultos que vivem com HIV/AIDS - Marchi, Maressa Claudia de (2014)
The goal was to evaluate the relations between social support and adherence to HAART in adults living with HIV/Aids, receiving care in Santa Maria University Hospital. A transversal study, with a quantitative approach, among 179 adults during antiretroviral treatment for HIV/Aids. The data collection was made from march to july in 2012, after the approval from the Ethics in Research Committee from UFSM under the CAAE number 0322.0.243.000-11. The instruments used in this subproject where HIV/Aids social support evaluation Scale and Evaluation questionary about adherence to antiretroviral treatment in people with HIV/Aids (CEAT-VIH). After verifying errors and inconsistencies, the statistical analysis was made with PASW Statistic® (Predictive Analytics Software, from SPSS Inc., Chicago USA ) version 18.0 for Windows. From the adults in antiretroviral treatment, 83,2% where defined as non-adherent ( raw score ≥ 83; percentile ≥ 85 ). The social support showed a mean general score of 87,71 (±19,2). Through this bi-variate analysis, it was shown that living with someone in a conjugal relationship is significantly associated with emotional and instrumental social support. The source of emotional and instrumental support was more frequently the partner, followed next by family living with the individual. It was identified that patients with strict adhesion to treatment showed significantly higher emotional support mean scores. Adhesion to treatment with antiretroviral therapy has a low positive correlation with emotional support (r=0,248; p=0,001) and a positive one with total social support (r=0,185; p=0,013). It was concluded that emotional support interferes in adhesion and it´s evaluation may contribute in detection of those individuals who will have major difficulties to antiretroviral therapy adherence, leading to the elaboration of strategies of care to this population.